2009
DOI: 10.3390/ijms10041590
|View full text |Cite
|
Sign up to set email alerts
|

Composition-Dependent Dielectric Properties of DMF-Water Mixtures by Molecular Dynamics Simulations

Abstract: Abstract:In this paper, we study the dielectric properties of water-N,N dimethylformamide (DMF) mixtures over the whole composition range using a molecular dynamics (MD) simulation. The static and microwave frequency-dependent dielectric properties of the mixtures are calculated from MD trajectories of at least 2 ns length and compared to those of available measurements. We find that the short-ranged structural correlation between neighboring water and DMF molecules strongly influences the static dielectric pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The hard double-charged cation is preferably solvated by water (the hardest of the solvents under consideration), and as its fraction in solution decreases, the nickel halide is salted out. The same result follows also from the formation of stable heteromolecular associates of water with organic solvent, which was confirmed by thermodynamic methods [15][16][17][18][19][20]. Similar effect is also observed for the other systems considered in this work.…”
supporting
confidence: 88%
“…The hard double-charged cation is preferably solvated by water (the hardest of the solvents under consideration), and as its fraction in solution decreases, the nickel halide is salted out. The same result follows also from the formation of stable heteromolecular associates of water with organic solvent, which was confirmed by thermodynamic methods [15][16][17][18][19][20]. Similar effect is also observed for the other systems considered in this work.…”
supporting
confidence: 88%
“…For DMF molecules, a modification of OPLS-AA was the Lennard-Jones parameters of carbon on methyl groups. With this modification H-bonds were found between DMF-water, 20,21 however, it was not tested with pure DMF.…”
Section: Introductionmentioning
confidence: 91%
“…However, the dielectric constant of the system decreases when the number of hydrogen bonds decreases. Jia et al 78 explored the static and microwave frequency dependent dielectric properties of water‐N,N‐dimethylformamide (DMF) mixtures over the entire composition range. It is found that hydrogen bond is one of the factors affecting the dielectric constant.…”
Section: Molecular Simulation Study Of Microwave‐assisted Azeotropic ...mentioning
confidence: 99%